Toward elevated light harvesting: efficient dye-sensitized solar cells with titanium dioxide/silica photoanodes1. Issue 57 (25th June 2015) - Yang, Peizhi; Tang, Qunwei; He, Benlin
<x xml:space="preserve">Abstract</x> Light harvesting titanium dioxide/silica photoanodes are used for dye-sensitized solar cells.